2021
DOI: 10.1029/2021jb022314
|View full text |Cite
|
Sign up to set email alerts
|

Does Earthquake Stress Drop Increase With Depth in the Crust?

Abstract: The stress release, or stress drop, during earthquake rupture has long been thought to be directly related to the magnitude of the ambient stress (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 66 publications
(171 reference statements)
2
24
0
Order By: Relevance
“…This is consistent with the previous results of AS2007. It is also in agreement with a recent multi-region analysis (Abercrombie et al, 2021) that showed that previously reported increases in stress drop with depth could potentially be artifacts of inadequate correction for depth dependent path effects.…”
Section: Implications For Stress Drop Scaling With Depth and Magnitudesupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with the previous results of AS2007. It is also in agreement with a recent multi-region analysis (Abercrombie et al, 2021) that showed that previously reported increases in stress drop with depth could potentially be artifacts of inadequate correction for depth dependent path effects.…”
Section: Implications For Stress Drop Scaling With Depth and Magnitudesupporting
confidence: 92%
“…The Spectral Decomposition process assumes a simple attenuation structure in the study region in which PT(t) depends only on the travel time. Any spatial variation in attenuation, including a dependence on source depth is not included, and will be absorbed into the event terms and bias the resulting source spectra (e.g., Abercrombie et al, 2021;Shearer et al, 2019). In other words, ET(t) in Equation 1 will include the real source term and a function that includes both common effects at all events and all sites, and source region specific attenuation.…”
Section: Spectral Decomposition To Obtain Relative Event Source Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…These two events occurred in the Salton Trough region in rapid succession on 26 August 2012, with the first one having a deeper hypocenter and higher stress drop than It is often difficult to disentangle the effects of source and path when considering depth trends in source properties. Abercrombie et al (2021) found that spectral decomposition approaches that do not explicitly account for hypocentral depth in their empirical path corrections can bias the observations toward an apparent depth trend in frequency content, since sources at greater depths will have seismic raypaths that preferentially sample deeper crustal rocks that are less attenuating. Our EGF selection process takes depth proximity into account and thus should mitigate potential artifacts of this form, lending some confidence that the observed depth trend is a real one.…”
Section: Discussionmentioning
confidence: 99%